Comparative assessment of echocardiographic parameters, including the left ventricular global function index in patients with myocardial infarction with obstructive (MICAD) and non-obstructive coronary artery disease (MINOCA) - N. I. Maksimov; I. S. Grishin; N. S. Grishina (Российский кардиологический журнал, 2025)
Aim. To assess the main parameters of transthoracic echocardiography, including the global function index in patients with myocardial infarction with obstructive (MICAD) and non-obstructive coronary artery disease (MINOCA).Material and methods. The study included 170 patients with a diagnosis of myocardial infarction were hospitalized and underwent inpatient treatment at the Cardiology Department № 1 of the Republican Clinical and Diagnostic Center, Izhevsk. Coronary angiography was performed on a Phillips Allure Clarity system. Based on the procedure results, the patients were divided into 2 following groups: 1 — MINOCA (n=73); 2 — MICAD (n=97), who underwent stenting. Echocardiography was performed using a Siemens Acuson CV70 (Germany) for all patients on the first day of the disease (before coronary angiography). The main parameters of the left ventricle (LV) geometry were assessed. LV ejection fraction (EF) was determined using the Simpson method. The LV global function index (LVGFI) was determined using the following formula: LVGFI=stroke volume/ ((LV end-diastolic volume (EDV) + LV end-systolic volume (ESV))/2 + LV volume) × 100%. Based on the echocardiography data, the patients were divided into 2 following subgroups: 1 — low GFI (<31,2%), 2 — normal GFI (>31,2%).Results. No differences in age were found. In the MINOCA group, there were more females — 57,6% vs 29,9%. Patients with MICAD more often had ST elevation and pathological Q wave — 70% vs 33%. Anterior wall MI was equally common. Patients with MICAD had a larger left atrium diameter and EDV. No differences were found in other echocardiographic parameters. EF was higher in patients in the MINOCA group (trend towards differences). Patients with low GFI in the MINOCA group are older, has a larger left atrium diameter, right atrium, end diastolic dimension, EDV, ESV, LV mass, and a higher rate of LV hypertrophy (40% vs 12,5%, p=0,008). LVEF in the low GFI MINOCA group was 55% (vs 64,9% in MICAD, p=0,004). In both subgroups, patients had the same frequency of ST elevation and pathological Q wave. Patients with low GFI, obstructive coronary artery disease and male sex more often had ST elevation and pathological Q wave.Conclusion. In patients with MINOCA, LV geometry parameters on the first day of the disease are better than in patients with MICAD due to lower values of the end-systolic dimension, EDV, ESV. Patients with low GFI had higher values of the end-diastolic dimension, EDV, ESV, LV mass, and more often had LV hypertrophy, lower EF. Patients with low GFI in the MICAD group compared to low GFI in MINOCA showed differences in sex (more often men), ST elevation rate, pathological Q wave, and a higher EDV.